MOF-199 and Ni-BTC: Synthesis, Physicochemical Properties, and Catalytic Activity in Oxidation of 5-Hydroxymethylfurfural - Herlina, Idra; Krisnandi, Yuni Krisyuningsih; Ridwan, Muhammad (Bulletin of Chemical Reaction Engineering & Catalysis, 2023)
Platform chemical 2,5-furandicarboxylic acid (FDCA) has potential applications to replace petroleum-based chemicals. Metal Organic Framework (MOF) can be used as a catalyst to oxidize 5-hydroxymethylfurfural (HMF), producing FDCA. MOF-199 and Ni-BTC were synthesized using solvothermal method with trimesic acid (benzene 1,3,5-tricarboxylic acid/H3BTC) as a linker and Cu or Ni as a metal nod. The physical and chemical properties of catalysts were discovered through characterization using  X-ray Diffraction (XRD), Fourier Transform Infra Red  (FT-IR), Thermogravimetric Analysis (TGA), Scanning Electron Microscopy - Energy Dispersive X-ray (SEM-EDX), and Ammonia Temperature-programmed Desorption (NH3-TPD). FDCA and its intermediate compounds were produced by converting HMF to FDCA in a small glass batch reactor. The yields of products were then determined by High-Performance Liquid Chromatography (HPLC). HPLC results indicated that there was no DFF (2,5-diformylfuran) signal, indicating that FDCA was formed by FFCA (5-formylfuroic acid) and HMFCA (5-hydroxymethylfuroic acid) formation reaction pathway. The maximum conversion (71%) was obtained using Ni-BTC as a catalyst at 130 °C for 5 h, with FDCA yield of 61.8%. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).